Traveling in the Grand Duchy of Lithuania in the 16th–17th Century. Mobility Conditions and Travellers’ Everyday Life - Tomas Čelkis (Revista Română pentru Studii Baltice şi Nordice, 2019)
The article analyses traveling conditions in the Grand Duchy of Lithuania in the 16th–17th century. It is aimed at establishing the reasons for the mobility of the GDL citizens in the period in question which were affected by social and economic changes as well as those related to the development of the urban network in the country. Several types of journeys have been distinguished which is indicative of the intensity of population mobility. The general road condition was far from excellent which affected their usability, particularly in wet spells. Attempts to ensure road maintenance and repairs were not equally distributed and not always timely. This was one of the factors accountable for the pace and comfort of traveling. The research also dwells on the everyday life on the road that both the citizens of the country and its visitors experienced as well as issues related to attacks on travellers and highway robberies.